Food waste matters - The policy implications and sustainability of food waste practices (Research, Society and Development, 2023)
Food waste has grown in the last couple of years and is recognized by the general public, governments, education, companies, and Non-Governmental Organizations (NGOs) to cause greenhouse emissions and resource reduction. In the food supply chain, food waste is generated at all levels. The purpose of this article is to use information from various scholarly articles to analyze the determinants of consumer food waste and the key elements that facilitate or hinder food waste activities. Furthermore, we briefly discuss the contributions of various theories in understanding food wastage. This analysis shows that food waste needs to be understood and tackled with the views of different disciplines because it is quite complex. Understanding the reasons behind food waste production would aid in the creation of food waste preventive measures and sustainability.